2015
DOI: 10.1103/physrevb.91.235134
|View full text |Cite
|
Sign up to set email alerts
|

Flat-band engineering of mobility edges

Abstract: Properly modulated flatband lattices have a divergent density of states at the flatband energy. Quasiperiodic modulations are known to host a metal insulator transition already in one space dimension. Their embedding into flatband geometries consequently allows for a precise engineering and fine tuning of mobility edges. We obtain analytic expressions for singular mobility edges for two flatband lattice examples. In particular, we engineer cases with arbitrarily small energy separations of mobility edge, zeroe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 32 publications
(35 reference statements)
0
49
0
Order By: Relevance
“…Such states thus belong to the U = 1 class of FBS as per the nomenclature introduced by Danieli et al [8]. However, the rule of constructing the distribution of amplitudes, as shown as an ex- Berker-diamond array in its 3rd generation.…”
Section: The Closed Loop Berker Geometrymentioning
confidence: 98%
See 2 more Smart Citations
“…Such states thus belong to the U = 1 class of FBS as per the nomenclature introduced by Danieli et al [8]. However, the rule of constructing the distribution of amplitudes, as shown as an ex- Berker-diamond array in its 3rd generation.…”
Section: The Closed Loop Berker Geometrymentioning
confidence: 98%
“…The density of packing may even lead, for a large enough generation of the hierarchical structure, to a re-entrant dispersive to non-dispersive crossover in the behavior of the electrons. A recent inspiring work by Danieli et al [8] has shown that a quasiperiodically modulated flat band geometry may even allow for a precise engineering of the mobility edges.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(13). Values of the phase, marked in the figure near the respective lattice sites, are φ1 = − arctan λ 2 − λ 2 − 1 / λ 2 + 1 and φ2 = − arctan λ 2 + 1 / λ 2 − 1 .…”
Section: Fig 4: Fb-cls Modes In the Linear System ψ (1)mentioning
confidence: 99%
“…The CLS existence has been experimentally probed in the same settings where FB lattices may be realized, as mentioned above: waveguiding arrays [7][8][9], exciton-polariton condensates [10], and atomic BECs [4]. The impact of various perturbations, such as disorder [5,11], correlated potentials [12,13], and external magnetic and electric fields [14], on FB lattices and the corresponding CLSs was studied too.…”
Section: Introductionmentioning
confidence: 99%